Comparative Analysis Of The Memorandum Of Agreement On The Ancestral Domain (MOA-AD) Aspect Of The GRP-MILF Tripoli Agreement On Peace Of 2001 And Framework Agreement On The Bangsamoro (FAB) - Candelaria, Sedfrey M (Archīum Ateneo, 2013)
Peace processes, which often culminate in the adoption of agreements, have been used traditionally in international law to end armed conflicts. The form within which negotiated settlements have been contained are primarily up to the negotiating parties to determine. However, the legal characterization of these agreements are independently and objectively governed by a set of rules either under the municipal legal system or at the level of international law. A peace treaty is an “agreement or contract made by belligerent powers, in which they agree to lay down their arms, and by which they stipulate the conditions of peace and regulate the manner in which it is to be restored and supported.”2 Apart from being a source of international obligations, treaties have been utilized at a national level to transfer territory, settle disputes, protect human rights, and regulate commercial relations.3 Peace agreements, as presently applied, are often used as a mode to end hostilities between a state and a non-state entity due to secessionist struggles or problems. This is especially so at a time when non-state entities are standing firm in their demands for self-determination as they incessantly fight for independence. Self-determination is supported by international law and embodied in international instruments such as the Charter of the United Nations, the International Covenant on Civil and Political Rights, and the International Covenant on Economic, Social and Cultural Rights. The great urge of peoples to determine their own economic, social, and cultural development causes opposition or hostilities within a state or nation. Therefore, peace agreements are relevant, particularly at the national level, in trying to resolve these hostilities. Most peace agreements have one common feature — they are used as a means to an end, which is to attain peace, by leading towards building a positive momentum for a final and comprehensive settlement. Peace agreements are generally “contracts intended to end a violent conflict, or to significantly transform a conflict, so that it can be more constructively addressed.”6 There are various types of peace agreements, each with their own distinct purpose. As to its components, most peace agreements address three main concerns: procedure, substance, and organization.12 The procedural components provide for the methods that establish and maintain peace such that they delineate the how of a peace process. 13 These include the setting up of schedules and institutions that “facilitate the implementation of substantive issues such as elections, justice, human rights and disarmament.”14 The substantive components provide for the changes to be made after the peace agreement is reached such as political, economic, and social structural changes that are needed to “remedy past grievances and provide for a more fair and equitable future.”15 The organizational or institutional components are mechanisms intended to “promote the peace consolidation efforts”16 such that they address the who aspect of the agreement.17 It can be gleaned then that although the main goal of peace agreements is to achieve peace or to end hostilities between or among parties, each and every peace agreement varies as to its procedural and substantive components. Peace agreements adopt various measures in addressing their own respective dilemmas and each has its own distinct way of enabling the parties involved in the agreement to cooperate and comply with the agreed terms to ensure the success of the measures adopted.